The Adoption of Internet of Things in Water Quality Measurement Community Service Project - Cucuk Wawan Budiyanto; Bangun Panduko Johan; Candra Zulkarnain; Raihanah Nurul Izzah; Indah Widiastuti; Aini Nazzura Paimin (FKIP Universitas Sebelas Maret, 2025)
Integrating Internet of Things (IoT) technology into education is increasingly vital in supporting environmental sustainability and developing green skills among students. This community service program focused on utilising IoT for water quality monitoring as part of extracurricular activities in a vocational school. The program aimed to enhance students’ understanding of environmental conservation and provide practical skills aligned with Industry 4.0 standards. The activities included preparation, IoT workshops, and hands-on implementation in the field, focusing on real-time monitoring of water parameters such as pH, Total Dissolved Solids (TDS), and temperature using IoT-based sensors. The results indicated that students became more aware of environmental issues and developed practical IoT and data analysis competencies. This initiative also highlighted the importance of IoT in enhancing competitive skills in the job market, particularly in sectors requiring sustainable practices. The adoption of IoT in education, especially in green skill camps, offers significant potential to prepare students for future challenges in environmental management and technological innovation.